The Application of Mental Health at Islamic Boarding Schools - Faisal Anwar; Putri Julia (International Conference on Multidisciplinary Research, 2022)
Islamic boarding schools are the central places for Islamic education in Indonesia. The schools have been producing Islamic leaders from time to time. Besides, they actively make an innovation so they will not be left behind. Parents sending their children into Islamic boarding schools generally expect that their children will be knowledgeable Muslim leaders in the future. However, there are factors that prevent some children from staying longer at the boarding schools. This research is a literature study with documentation research methods since the data were obtained in the form of writing, words, pictures, photos with the type of literature study by collecting, reviewing and analyzing data, documents or works related to the object of research. It was found that strict rules are among the main reasons. The students admitted that they were not mentally strong to face the rules. Other factors were loss, truancy, violence, and homosexuality. Thus, it is suggested that Islamic boarding schools should adopt the mental health perspective into their teaching and address the aforementioned issues, allowing the students to feel comfortable and be willing to stay longer at the school. Keywords: Mental health, Islamic Boarding Schools, Application